Massage Therapy as a Strategy for Managing Stress and Physical Symptoms in Pre-Menopause Women - Elok Mardliyana, Nova; Adyani, Asta; Puspita, Irma Maya (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Pre-menopause is a transitional phase characterized by decreased estrogen and triggers various physical and psychological complaints, such as hot flashes, sleep disturbances, muscle pain, fatigue, and stress, that can reduce women’s quality of life and productiv ity. Massage therapy, as a non-pharmacological intervention, is known to reduce cortisollevels, increase endorphins, improve blood circulation, and promote musclerelaxation, potentially effectively reducing stress and physical complaints in premenopausal women at the community level. This study aims to analyze the effectiveness of massage therapy in reducing stress and physical symptoms among premenopausal women. Subjects and Method: This quasi-experimental study involved 64 premenopausal women members of Ibu Aisyiyah Mulyorejo group who were divided into an intervention group (n=32) who received massage therapy and a control group (n=32) without massage. Massage therapy was given twice a week for 30–45 minutes per session, while changes in physical and psychological complaints were measured using the Menopause Rating Scale (MRS) before and after the intervention and analyzed using the Wilcoxon and Mann–Whitney tests at a significance level of p<0.05. Results: Before the intervention, 97% of respondents in the intervention group were classified as having severe complaints, while 3% were in the moderate category. Following massage therapy, all respondents demonstrated improvement, with 75% categorized as having moderate complaints and 25% as having mild complaints, and no participants remaining in the severe category. The Wilcoxon test indicated a significant reduction in MRS scores within the intervention group (p = 0.002; r = 0.87), while the Mann–Whitney test showed that post-intervention MRS scores in the intervention group were significantly lower than those in the control group (p = 0.005). Conclusion: Massage therapy is effective in reducing psychological and physical complaints in premenopausal women and can be recommended as a community-based complementary strategy for managing stress and somatic symptoms in this group